Vowel lengthening as the default strategy of arabization: Phonological adaptation of English culinary loanwords in Arabic digital media - Husnul Khatimah; Nurain; Arini Alfa Mawaddah; Amal Syahidin (Diwan: Jurnal Bahasa dan Sastra Arab, 2026)
Although the rapid proliferation of Arabic-language digital media platforms has significantly accelerated the process of arabization of English culinary vocabulary, the underlying phonological mechanisms have not been systematically studied in a digital domain-specific context. Addressing this gap, this study identifies and analyzes patterns of vowel change from English to Arabic in the maṭbakh section of the sayidaty.net website, using al-Jawaliqi's arabization theory as the primary analytical framework. A qualitative descriptive design was adopted, with data comprising English culinary loanwords sourced from the maṭbakh rubric of sayidaty.net. Data were collected through systematic non-participant observation and documented using structured note-taking techniques, then analyzed using distributional methods and translational equivalent methods with the International Phonetic Alphabet transcription system. The results show that the nine English vowel phonemes [i], [ɪ], [e], [ɛ], [æ], [a], [ə], [ʊ], and [ʌ] produce 21 distinct phonological adaptation patterns out of 112 instances found. Three cross-phonemic rules emerged as dominant: systematic vowel lengthening as the default strategy of arabization; lexical stress sensitivity; and segmental conditionality. This research contributes to the development of a domain-specific phonological model of arabization that extends al-Jawaliqi's classical framework with the dimension of contextual conditionality, while establishing a replicable methodology for the study of vowel adaptation on Arabic digital media platforms.